The Resilient Thread: Digital Archiving and the Semantic Revitalization of Palembang's Songket Weaving Traditions - Dian Rahayu; Iqbal Anugerah; Henry Peter Paul (Enigma Institute, 2024)
Palembang's Songket, a UNESCO-recognized Intangible Cultural Heritage, faces significant threats from modernization and the gradual erosion of its tacit knowledge, particularly the philosophical meanings embedded within its motifs. This study addressed the urgent need for a preservation model that transcends simple digitization by focusing on semantic revitalization. This research employed a multi-phase, mixed-methods approach conducted between 2023 and 2025. We developed a comprehensive digital archive through high-resolution photogrammetry of 150 heritage Songket textiles and ethnographic fieldwork, including in-depth interviews with 15 master weavers in Palembang. A bespoke semantic ontology was constructed using Web Ontology Language (OWL) to map the complex relationships between motifs, techniques, materials, and their socio-cultural meanings. This ontology formed the backbone of an interactive web-based platform,